2007
DOI: 10.1002/jbm.a.31171
|View full text |Cite
|
Sign up to set email alerts
|

Human neutrophil elastase and collagenase sequestration with phosphorylated cotton wound dressings

Abstract: The design and preparation of wound dressings that redress the protease imbalance in chronic wounds is an important goal of wound healing and medical materials science. Chronic wounds contain high levels of tissue and cytokine-destroying proteases including matrix metalloprotease and neutrophil elastase. Thus, the lowering of excessive protease levels in the wound environment by wound dressing sequestration prevents the breakdown of extracellular matrix proteins and growth factors necessary for wound healing. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 37 publications
1
33
0
1
Order By: Relevance
“…Assessment of the phosphorylated cotton gauze's protease-lowering efficacy, when cured under stationary oven conditions, showed that DAP : urea at a percent ratio by weight of 30 : 10 (urea : PO4) gave higher protease-lowering activity when compared with SMP as the phosphorylating reagent (Figure 4(a) and (d)). This result of higher add-ons correlating with better protease sequestrant efficacy is consistent with previous work, where the increase in cellulose phosphorylation was correlated to an increase in protease sequestrant efficacy [16]. Thus, to improve whiteness and retain efficacy a series of formulations containing a combination of DAP and SMP were cured on the cotton gauze.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Assessment of the phosphorylated cotton gauze's protease-lowering efficacy, when cured under stationary oven conditions, showed that DAP : urea at a percent ratio by weight of 30 : 10 (urea : PO4) gave higher protease-lowering activity when compared with SMP as the phosphorylating reagent (Figure 4(a) and (d)). This result of higher add-ons correlating with better protease sequestrant efficacy is consistent with previous work, where the increase in cellulose phosphorylation was correlated to an increase in protease sequestrant efficacy [16]. Thus, to improve whiteness and retain efficacy a series of formulations containing a combination of DAP and SMP were cured on the cotton gauze.…”
Section: Resultssupporting
confidence: 91%
“…Urea promotes the biphasic reaction between the cellulose and the phosphorylating reagent (see reaction schematic shown in Figure 3), and the release of ammonia from urea decomposition during the reaction required engineering exhaustion of ammonia from the curing oven (see conditions stated in Figure 2 inset). The effect of the two different finishes on the protease sequestrant efficacy of the phosphorylated cotton wound dressing has been previously reported [16]. The typical temperature range for assessing the curing conditions with SMP was 160-175 C.…”
Section: Resultsmentioning
confidence: 99%
“…These proteases, including MMPs and neutrophil elastase, augment tissue and cytokine destruction. Products which lower the levels of these proteases in the wound environment help to prevent the breakdown of extracellular matrix proteins and growth factors that are crucial for wound repair . In a study by Edwards and Howley in 2007, phosphorylated cotton dressings were tested for their ability to sequester elastase and collagenase activity in vitro.…”
Section: Resultsmentioning
confidence: 99%
“…Inhibition of tissue proteases by biomaterials has traditionally been demonstrated using solid‐state assays, whereby the intact samples are incubated in enzyme solutions and then the residual enzyme activity quantified following removal of the sample (14–19,22,29). In the case of soluble or partially soluble biomaterials, such as OFM and ORC/C, reductions in enzyme activity using this approach can be accounted for either by (i) surface adsorption of the enzyme to the biomaterial; or (ii) dissolution of soluble inhibitory components.…”
Section: Discussionmentioning
confidence: 99%